Reducing the 10-year risk of ischemic cardiovascular disease to receive early cardiovascular benefits from bariatric surgery for obesity in China - Li, Yinhui; Liu, Jia; Zhou, Biao; Li, Xiaohui; Wu, Zhenyu; Meng, Hua; Wang, Guang (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiovascular risk due to obesity can be improved greatly by bariatric surgery. However, there is no research involving appropriate model for evaluating cardiovascular disease risk reduction in bariatric surgery for obesity in China. We selected the ischemic cardiovascular disease (ICVD) risk score that accurately predict cardiovascular risk in Chinese adults to evaluate the 10-year risk of ICVD and estimated early cardiovascular benefits of bariatric surgery in obese Chinese patients through its reduction. Methods: From 2017 to 2019 we followed up 107 patients 6 months after surgery and measured the ICVD 10-year risk and other cardiovascular factors before and after surgery. Results: There were significant reductions in the ICVD total score( p<0.001) and ICVD 10-year risk (%) (p<0.001) 6 months postoperation compared with baseline. Furthermore, we found significant reductions in body mass index (BMI), body adiposity index (BAI), low-density lipoprotein (LDL), small dense-low-density lipoprotein (sd-LDL) and triglycerides (TG) 6 months after surgery compared with preoperation(all p<0.05). The decrease in ICVD total score was correlated with excess BMI loss (%EBMIL), reduced BAI, reduced LDL, reduced sd-LDL and reduced TG respectively(all p<0.05) at 6 months postoperation. Moreover, there were significant reductions in the ICVD total score in the male subgroup [3 (3, 5) vs 2.5 (2, 4), p<0.001] and female subgroup [3 (2,4) vs 2 (1, 3), p<0.001] 6 months postoperation compared with baseline. At last there were also significant reductions in the ICVD total score in the diabetic subgroup [5 (4, 6) vs 4 (3, 5), p<0.001] and nondiabetic subgroup [2 (2,3) vs 2 (1, 2), p<0.001] 6 months postoperation compared with baseline. Conclusions: Bariatric surgery could provide early cardiovascular benefits for patients with obesity in China by reducing the 10-year risk of ICVD. Both men and women with obesity achieved cardiovascular benefits according to bariatric surgery, so did diabetic and nondiabetic patients.